Lung Absess With Complication of Bronchopleural Fistula in A Patient With Type 2 Diabetes mellitus at Klungkung Regional Hospital - Wedanta Mahadewi, I Gusti Agung; Ari Sepriyanti, Ni Komang; Putu Ekaruna, Ida Bagus (Greenation Publisher & Yayasan Global Research National, 2024)
Lung abscess is a clinical condition characterized by the accumulation of purulent material in the necrotic lung parenchyma. One of the complications is a bronchopleural fistula, which is an abnormal channel that connects the bronchus to the pleural cavity. KS, a 65 years old male, presented with complaints of intermittent shortness of breath for 3 months, which had worsened the day before hospital admission. The patient also reported fever and cough with foul-smelling phlegm for 1 week. Physical examination revealed tachypnea and decreased breath sounds in the right intercostal spaces 3-6. Laboratory examination showed anemia, leukocytosis, and hyperglycemia. A plain chest radiograph revealed a loculated right pleural effusion, with suspected empyema, and a chest CT scan with contrast showed pneumonia with suppurative fluidopneumothorax and fistulation into the bronchus. Examination of the patient's pleural fluid revealed increased ADA test results and isolation of Candida spp on culture. Additional tests showed that MTB was not detected, and the IGRA was negative. Patient management included antibiotics, transfusions, and insulin administration. A bronchopleural fistula is a complication of a lung abscess that occurs when a channel forms from the abscess to the bronchus, creating a sinus between the main branch of the bronchus, lobe, or bronchial segment and the pleural space. Management includes controlling infection, treating respiratory dysfunction, and controlling air leaks. A 65-year-old male patient with a history of type 2 diabetes mellitus complained of coughing and shortness of breath for 3 months, which had worsened over the past week. Examination revealed a lung abscess with a bronchopleural fistula. Therapy included antibiotics to eradicate the infection and thoracentesis to treat respiratory dysfunction.